The Characteristics of Persian Historical Gardens (Case Study: Emarat Birooni Garden of Urmia, Iran) - Gachkar, Sadaf; Gachkar, Darya; Abbaszadeh, Mozafar; Aghlmand, Soheila; Sattary, Sattar (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2022)
Persian gardens are valuable historical and cultural human-built landscapes however, Persian gardens are deteriorating gradually. Thus, comprehensive studies would be helpful in obtaining deeper insights into different aspects and meaning of Persian gardens. The descriptive-analytical approach was used to review the EmaratBirooni garden of Urmia (Campus of Urmia University) as it is the only remnant of Qajar period demonstrating a clear image of the past of the Persian garden model in Urmia. Data were employed through literature review and on-site field study. It was found that the Campus of Urmia University had three historical eras- era 1: Before the garden was purchased by American missionaries, era 2: The settlement of American missionaries, era 3: After American missionaries left and delivered the garden to the government. By examining the periods, it was seen that the survival of the campus stemmed from proper uses in each era. This suggests that new uses suiting the contemporary conditions could be beneficial in protecting historical gardens. In this respect, it is essential to protect historical gardens since these gardens can become a cultural capital to the future generations.